PENGATURAN PEMILIHAN KEPALA PEMERINTAH NEGERI DI KABUPATEN MALUKU TENGAH - Sherlock H Lekipiouw; Natanel Lainsamputty; Yohanes Pattinasarany; Hendrik Salmon (LPPM Universitas Ekasakti Padang, 2022)
ABSTRACT The development of the regional government system has undergone substantial changes with the birth of Law Number 6 of 2014 concerning Villages. The regulation regarding the election of village heads has changed with a simultaneous election mechanism and the candidate who gets the most votes is entitled to be appointed as village head. The purpose of this study is to examine and analyze the regulation by mechanical election in the district of Maluku Tengah which in the Regional Regulation Number 03 of 2006 concerning Procedures for the Nomination, Election and Inauguration of the Head of the Negeri Government whose substance the article on elections still refers to Law Number 32 of 2014 which is no longer valid. The method used in this research is the socio-legal method whose data are taken from the interview process and study of Regional Regulation documents and by using literacy related to the research title.